Turning the Mre11/Rad50 DNA repair complex on its head: lessons from SMC protein hinges, dynamic coiled-coil movements and DNA loop-extrusion?. (18th December 2020) - Zabolotnaya, Ekaterina; Mela, Ioanna; Henderson, Robert M.; Robinson, Nicholas P.
Abstract : The bacterial SbcC/SbcD DNA repair proteins were identified over a quarter of a century ago. Following the subsequent identification of the homologous Mre11/Rad50 complex in the eukaryotes and archaea, it has become clear that this conserved chromosomal processing machinery is central to DNA repair pathways and the maintenance of genomic stability in all forms of life. A number of experimental studies have explored this intriguing genome surveillance machinery, yielding significant insights and providing conceptual advances towards our understanding of how this complex operates to mediate DNA repair. However, the inherent complexity and dynamic nature of this chromosome-manipulating machinery continue to obfuscate experimental interrogations, and details regarding the precise mechanisms that underpin the critical repair events remain unanswered. This review will summarize our current understanding of the dramatic structural changes that occur in Mre11/Rad50 complex to mediate chromosomal tethering and accomplish the associated DNA processing events. In addition, undetermined mechanistic aspects of the DNA enzymatic pathways driven by this vital yet enigmatic chromosomal surveillance and repair apparatus will be discussed. In particular, novel and putative models of DNA damage recognition will be considered and comparisons will be made between the modes of action of the Rad50 protein and other related ATPases of the overarching SMC superfamily.